Dynamic crack propagation in specimens with a surface irregularity - Ali Hassanirad; Vahid Vaziri; Ko-Choong Woo; Marian Wiercigroch (Vietnam Journal of Mechanics)
Initiation of cracks and their propagation in prescribed orientations on tubular specimens has been made possible on a dynamic fatigue testing rig developed at the University of Aberdeen. This rig was originally designed to perform experiments on single edge notched beams (SENB) [1,2]. Modifications have recently been made so as to accommodate experimental tests on tubular specimens with a range of sizes and other cross sections. Crack initiation at grooves on such specimens has been followed by crack growth. At the same time, lateral oscillations of cracked specimen have been measured, as well as accelerations of base excitation, masses above and below cracked specimen. Forces on these two masses have been observed by two load cells attached at positions close to specimen. These load cells facilitated the measurement of stresses in experiment. Crack length time histories have also been constructed by applying an alternating current potential difference (ACPD) method. Fatigue cracks were initiated at the pre-cut grooves in aluminium tubular specimens. Three specimens with different groove sizes were tested in fifteen individual experiments. A three-dimensional Finite Element model was established for each specimen so as to calculate the stress concentration factor (SCF). This formed the basis of determining the amplitude of forcing input made possible by an electromechanical shaker. The phase shifts of acquired time histories has provided some indication of energy transfer mechanism during fatigue and system dynamic response. Observations of cracked specimen displacement during experiments was compared against calculated displacement from elastic theory. Nonlinear responses were observed, suggesting nonlinear stiffness characteristics of the specimen due to discontinuities introduced by crack growth and plasticity effects. Comparison of damage combinations in experimental observation was made with predictions from BS EN 1999-1-3. All experimental observations of total damage combination were higher than predicted values by the latter code.